INFLUENCE THERAPY GUIDED IMAGERY ON THE INTENSITY OF MOTHER'S PAIN POST SECTIO CAESAREA - Pertami, Sumirah Budi; Hidayah, Nurul; Solikhah, Fitriana Kurniasari (Indonesian Journal of Applied Health, 2024)
Sectio caesarea is a surgery to deliver the fetus through an incision in the abdominal wall. Post caesarean section pain can be reduced with pharmacological and non- pharmacological measures . The non-pharmacological measures studied in this research were guided imagery . The aim of this study was to determine the effect of giving a combination of guided imagery therapy on the intensity of maternal pain after caesarean section. This research design uses a Quasy Experiment. The sampling technique used was non-probability sampling, purposive sampling type with a total of 32 respondents. The results of the research in the treatment group showed that most of the results (81.4%) were on a mild pain scale and in the control group most of them (100%) were on a moderate pain scale . The results of the Wilcoxon rank-sum test in the treatment group were Sig. (2-tailed) = 0.000, which means that there is a significant influence on the intensity of pain before and after the administration of guided imagery on the pain intensity of mothers post caesarean section. The Man Withney test result is Sig. (2-tailed) = 0.000, which means that H0 is rejected. H1 is accepted. There is a significant difference in pain intensity between the treatment group and the control group. It is hoped that post-cesarean section mothers will use this combination of therapy to help relieve the pain they are experiencing.